HYDROGEOLOGICAL ASSESSMENT OF THE SALINIZATION PROBLEM OF XILAGANI - IMEROS AQUIFER SYSTEM IN SW PLAIN AREA OF RHODOPE PREFECTURE, GREECE - Pliakas, F.; Mouzaliotis, A.; Kallioras, A.; Diamantis, I. (Bulletin of the Geological Society of Greece, 2007)
This paper investigates the progress of groundwater salinization within the plain area ofXilagani - Imeros, in SW part ofRhodope Prefecture, as well as the suitability of groundwater for drinking and irrigation use, after qualitative classification of groundwater samples from selective wells of the study area based on relevant guidelines. Some managerial suggestions for the confrontation of the seawater intrusion regime of the study area are also included. The investigation in question took place between 1994-1997 and 2002-2006, and involved drilling of test wells, geoelectric sounding measurements, grain size analyses, elaboration of hydro logical data, monitoring and relevant analysis of the groundwater level fluctuations in selective wells, electrical conductivity measurements as well as conducting chemical analyses of water samples from selective wells of the study area and relevant elaboration.